Feasibility Analysis of UMKM Bakso Mas Eko and Rawasikut Karawang Swimming Pool - Malika Hayatun Nisa; Dedi Mulyadi; Santi Pertiwi Hari Sandi (International Journal of Economics and Management Research, 2025)
This study uses the Quantitative Descriptive method, sample selection is carried out by purposive sampling method, namely the researcher chooses MSMEs Bakso Mas Eko Rawasikut Karawang. The purpose of this study is to know, analyze, calculate and explain how the business feasibility of Bakso Mas Eko Rawasikut Karawang MSMEs and how the business feasibility of the Rawasikut Karawang swimming pool. Data was collected through observation, interviews and documentation. The results of this study show that Bakso Mas Eko and Rawasikut Karawang Swimming Pool MSMEs are declared feasible, because the results of the NPV calculation are positive and the Profitability Index value is PI>1. In the business feasibility of MSMEs Bakso Mas Eko Rawasikut and Rawasikut Karawang Swimming Pool, the results of the analysis show that it is more feasible to develop between Bakso Mas Eko Rawasikut and Rawasikut Swimming Pool, namely Bakso Mas Eko Rawasikut through the calculation of its financial feasibility.